2009
DOI: 10.1016/j.physc.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Critical current of laminated and non-laminated BSCCO superconducting composite tape under bending strain

Abstract: a b s t r a c tIt has been reported that, when the (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O x (hereafter noted as BSCCO)/Ag/Ag-alloy tape is laminated with stainless steel, the tensile strain tolerance of critical current is much improved. In this study, using the non-laminated and laminated BSCCO composite tapes fabricated at American Superconductor Corporation, the influences of lamination on the critical current and its distribution under bending strain were studied. The analysis of the measured variation of average crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…3 compares the relationship between the stress and strain at 77 K, and that between the normalized critical current at the tively. These values correspond well with previously reported results where the fracture strain of the filament almost doubled owing to lamination [9][10][11]. In the next section, the maximum fatigue stress for SUS3ply tapes is selected according to the irreversible stress under the loading step, r l,irr95% , of 342 MPa, and that under the unloading step, r u,irr99% , of 315 MPa.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…3 compares the relationship between the stress and strain at 77 K, and that between the normalized critical current at the tively. These values correspond well with previously reported results where the fracture strain of the filament almost doubled owing to lamination [9][10][11]. In the next section, the maximum fatigue stress for SUS3ply tapes is selected according to the irreversible stress under the loading step, r l,irr95% , of 342 MPa, and that under the unloading step, r u,irr99% , of 315 MPa.…”
Section: Resultssupporting
confidence: 88%
“…It is also reported that the lamination suppresses the fracture of Bi2223 filaments. Consequently, the fracture strain of Bi2223 filaments in the laminated composite tapes is twice as much as that of filaments in the non-laminated composite tapes [9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…During the search for the cause of lower local I c values, two main mechanisms were identified in the investigations carried out by various groups: a weakening of vortex pinning in the superconducting layer, and a reduction of its cross-section [21][22][23][24][25][26]. If the properties of the superconducting material vary, the power-law exponent, n, is expected to fluctuate along the tape length [27][28][29].…”
Section: Statistical Analysis and Evaluation Of The Overall Critical ...mentioning
confidence: 99%